Lessons in becoming myself - Burstyn, Ellen, 1932- (New York : Riverhead Books, 2006)
In this story of a woman's search for a deeper understanding of herself, actress Burstyn explores the unexpected paths her life has taken. Born in Detroit during the Depression, she left home at eighteen, leaving behind a complicated relationship with her mother, to become a model. Eventually, she ended up on Broadway and on television in the late 1950s and early 1960s before turning to film. She delivered brilliant performances in The Last Picture Show; The Exorcist; Alice Doesn't Live Here Anymore, for which she won an Academy Award; Resurrection; and Requiem for a Dream. This book is a frank and unsparing account of Burstyn's search for personal and professional authenticity, the story of the quest for the examined life. Raised a Catholic, she has spent her life exploring a range of spiritual experience--from the Himalayas to Cambodia, from Mont Blanc to New York City--that goes deeper than labels. Provided by the publisher.
Keywords: Burstyn, Ellen, -- 1932-; Actors -- United States -- Biography